(3EOGQI GdUa dOi eYdeGJ QjGV GdCWaGd hCKQgG bj Sdhcge aj HYV eOGQS UjOG (B((3dHfGf(B)s - g ((3HjQhJs (3LGeYI GdbOjS jhSas, 2011)
(3JSYi GdOQGSI GdMGdjI Edi(B: 1) (3EdbGA GdVhA Ydi hGbY GdEOGQI GdUajI aj eOGQS UjOG (B((3dHfGf(B) (3hCf JHjf eOi GfSLGe gPg GdEOGQI eY GdJUhQGJ GdfXQjI GdJj cJHJ Mhd gPG GdehVhY(B. 2) (3JMOjO GdaQhbGJ GdbGFeI Hjf GdeQHjGJ aj cjajI EOGQJgf dUaha GdQhVI(B. 3) (3OQGSI GdYdGbI GdJj JQHW EOGQI GdeQHjGJ dUaha GdQhVI HGdeDgd GdYdej(B. 4) (3OQGSI GdYdGbI GdJj JQHW Hjf EOGQI GdeQHjGJ dUaha GdQhVI hNHQJgf GdYedjI(B. 5) (3OQGSI GdYdGbI GdJj JQHW Hjf EOGQI GdUa heYJbOGJ GdeQHjI(B. (3Je GNJjGQ YjfI GdOQGSI ef efWbI UjOG aj eOQSJjf JNJdaGf ajeG HjfgeG ef fhGM eJYOOI aEMOGgeG NGUI eOahYI hGdCNQi NGUI eLGfjI(B. (3GdChdi JVe CWaGdkG jCJhf ef HjFGJ ejShQI HGdELeGd, CeG GdKGfjI aJVe CWaGdkG ef YGFdGJ PGJ eSJhi Ohf GdhSW(B. (3aJchfJ GdYjfI ef GdeQHjGJ hGdCWaGd aj Uaha GdQhVI GdChdi aj cdJG GdeOQSJjf(B. (3CeG GdCOhGJ GdeSJNOeI acGfJ Ydi GdfMh GdJGdj(B: 1) (3COGI (BFlanders(3, (B2) (3ENJHGQ (BSutter-Eyeberg (3dJbjje SdhcjGJ GdJdGejP(B. (3CXgQJ fJGFL gPg GdOQGSI Cf gfGc aQhbGJ OGdI Hjf GdeQHjGJ aj cjajI EOGQJgf dUaha GdQhVI, jecf EQLGYgG Edi GdNHQI GdYedjI HTcd fSHj hEdi eYJbOGJ GdeQHjGJ hCSdhHgf HTcd cdj(B. (3ceG Je GcJTGa eG bO dG jhGab GdcKjQ ef GdOQGSGJ GdSGHbI hgj acQI Cf GdeDgd GdYdej hMOg dG jYde GdeQHj cjajI EOGQI GdUa, hEfeG jJjM dg eYQaI NUGFU feh GdCWaGd aj gPg GdeQMdI, hgPG dG jYfj Cf GdeQHjI SJeJdc GdCSdhH GdPj jeqcfgG ef GdJYGed eY GdCWaGd HGdWQjbI GdUMjMI(B. (3Ef ddNHQI OhkQG aj EMOGK aQb Hjf eQHjI hCNQi aj cjajI EOGQJgG dUa GdQhVI, haj LYd GdeQHjI CcKQ bOQI Ydi EOGQI GdUa Edi MO eYjf(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Class Management; Gestion d$1 (Bune classes; Kindergarten; Les Attitudes et conceptions des enseignants; Maternelle; Teachers attitudes and conceptions; (3GOGQI GdUas; (3QjGV GdCWaGds; (3UjOGs; (3ehGba GdeYdejf hJUhQGJges